Phenomenological approach to eating disorders: a scoping review - Eduardo Barreto Fernandes Silva; Monalisa de Fátima Rodrigues Pimenta Teles; Nayana Leão e Silva de Castro; Camila Pereira de Souza; Lucas Guimarães Bloc (Frontiers in Psychology)
Eating disorders are defined as persistent eating disturbances that compromise physical health and psychosocial functioning. Many of the patients transition between different diagnostic categories and have high mortality rates, which highlights the complexity of these illnesses. Using scientific literature, this study aimed to identify the contributions of the phenomenological approach related to eating disorders. A total of 30 articles were selected for analysis after adopting eligibility criteria that included: studies with effective publication status; published between 2013 and 2024; and available in Portuguese, French and/or English. The collection revealed a significant predominance of discussions about anorexia nervosa, followed by binge eating and bulimia. Through analysis, the following discursive themes were listed: corporeality; identity and relationship with others; proprioception and eating behavior; and clinical treatments. It is concluded that these findings highlight a need for treatment perspectives to consider the bodily experience in patients of eating disorders and its relations with otherness and oneself. It is considered that the modes of being in the diagnoses of Pica, Rumination and ARFID should be taken account in further research, as such works could elucidate questions on the nature of eating disorders.